2013
DOI: 10.3324/haematol.2012.074252
|View full text |Cite
|
Sign up to set email alerts
|

Somatic hypermutation analysis in follicular lymphoma provides evidence suggesting bidirectional cell migration between lymph node and bone marrow during disease progression and relapse

Abstract: ABSTRACTdeveloped algorithm to describe clonal hierarchy and migration patterns more thoroughly. Methods Patients, histology, and immunohistochemistryThis study comprised three patients with synchronous LN and BM infiltration by FL at presentation. Biopsies were performed during the diagnostic and staging procedures. The selection criteria were the diagnosis of FL according to the fourth edition of the WHO Classification of Tumours of Haematopoietic and Lymphoid Tissues.1 Clinical information was obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 51 publications
3
24
0
Order By: Relevance
“…Deregulated BCL2 expression likely confers resistance to apoptosis and allows the acquisition of further aberrations required for the full malignant transformation and FL progression . In addition, recent analysis of IgH gene mutations in specimens from lymph nodes and the bone marrow from three FL patients suggests bidirectional cell migration between the two compartments during disease progression and relapse, further substantiating the complexity of FL evolution .…”
Section: Discussionmentioning
confidence: 88%
“…Deregulated BCL2 expression likely confers resistance to apoptosis and allows the acquisition of further aberrations required for the full malignant transformation and FL progression . In addition, recent analysis of IgH gene mutations in specimens from lymph nodes and the bone marrow from three FL patients suggests bidirectional cell migration between the two compartments during disease progression and relapse, further substantiating the complexity of FL evolution .…”
Section: Discussionmentioning
confidence: 88%
“…Extensive mutation analysis of original lymphoma samples and their paired samples taken during late relapses might also be informative. 17 These authors suggest that relatively fewer mutated FL cells may find a niche in the bone marrow. These cells may be relatively quiescent and in consequence escape the effect of chemotherapy, and may repopulate the body after therapy ("founder cells").…”
mentioning
confidence: 99%
“…3). This high level of SHM can be found in FLs (Gagyi et al 2008;Wartenberg et al 2013;Carlotti et al 2015).…”
Section: Analysis Of Shm Of Ig Genesmentioning
confidence: 68%
“…Given that the B-ALL/LBL clearly emerged from the FL as evidenced by the fluorescence in situ hybridization (FISH) and WES data (please see the paragraphs below), this lack of an identifiable dominant clone at the B-ALL/LBL stage likely stems from the extreme SHM upon the disease progression. SHM in advanced FL or, in particular, transformed to diffuse large B-cell lymphoma can be very extensive (Wartenberg et al 2013;Carlotti et al 2015), even involving non-Ig gene loci (Pasqualucci et al 2001;Rossi et al 2006). Accordingly, lineage tracing of the dominant FL rearrangement in our case showed that some B-ALL/LBL clones were identified in distal portions and even in distinct branches of the FL lineage tree (Fig.…”
Section: Molecular Case Studiesmentioning
confidence: 99%